Can the UK achieve net-zero greenhouse gas emissions by 2050? - Castle, JL; Hendry, DF (University of Oxford, 2021)
Net-zero greenhouse gas emissions by 2050, the UK’s current target, requires bridging a dramatic energy transition and eliminating all other net sources of emissions while ensuring a just transition. Key components like renewable electricity generation and electric vehicles are well developed, but many issues remain. Public support for a green economy may wane if the economic costs are too high or seen as unfair, so although renewable energy is cheaper than fossil fuels, it is essential to maintain employment, real per-capita growth and reduced inequality. Decarbonizing the UK economy requires an integrated sequential approach and need not be delayed while dealing with the aftermath of the Covid-19 pandemic, energy crisis and resulting inflation.